(untitled) - Koop, C. Everett (Grand Rapids, Michigan, 1992)
Contents: Becoming a doctor, Becoming a surgeon, Becoming surgeon general, Great issuses, The surgeon general reports.
Keywords: Bác sĩ nhi khoa,Pediatric surgeons; Tiểu sử,Biography; Hoa Kỳ,United States